Organic Solute Transporter Alpha Deficiency: A Disorder With Cholestasis, Liver Fibrosis, and Congenital Diarrhea. - Gao, Emily; Cheema, Huma; Waheed, Nadia; Mushtaq, Iqra; Erden, Nihan; Nelson-Williams, Carol; Jain, Dhanpat; Soroka, Carol J; Boyer, James L; Khalil, Youssef; Clayton, Peter T; Mistry, Pramod K; et al. (Hepatology, 2020)
Keywords: Child, Preschool; Cholestasis; Diarrhea; Humans; Liver; Liver Cirrhosis; Male; Mutation; Pedigree; Receptors, G-Protein-Coupled

FOXP3 mutations causing early-onset insulin-requiring diabetes but without other features of immune dysregulation, polyendocrinopathy, enteropathy, X-linked syndrome. - Hwang, Jessica L; Park, Soo-Young; Ye, Honggang; Sanyoura, May; Pastore, Ashley N; Carmody, David; Del Gaudio, Daniela; Wilson, Janna F; Hanis, Craig L; Liu, Xiaoming; Atzmon, Gil; Glaser, Benjamin; et al. (Pediatr Diabetes, 2018)
Diabetes occurs in 1/90 000 to 1/160 000 births and when diagnosed under 6 months of age is very likely to have a primary genetic cause. FOXP3 encodes a transcription factor critical for T regulatory cell function and mutations are known to cause "immune dysregulation, polyendocrinopathy (including insulin-requiring diabetes), enteropathy, X-linked" (IPEX) syndrome. This condition is often fatal unless patients receive a bone-marrow transplant. Here we describe the phenotype of male neonates and infants who had insulin-requiring diabetes without other features of IPEX syndrome and were found to have mutations in FOXP3. Whole-exome or next generation sequencing of genes of interest was carried out in subjects with isolated neonatal diabetes without a known genetic cause. RT-PCR was carried out to investigate the effects on RNA splicing of a novel intronic splice-site variant. Four male subjects were found to have FOXP3 variants in the hemizygous state: p.Arg114Trp, p.Arg347His, p.Lys393Met, and c.1044+5G>A which was detected in 2 unrelated probands and in a brother diagnosed with diabetes at 2.1 years of age. Of these, p.Arg114Trp is likely a benign rare variant found in individuals of Ashkenazi Jewish ancestry and p.Arg347His has been previously described in patients with classic IPEX syndrome. The p.Lys393Met and c.1044+5G>A variants are novel to this study. RT-PCR studies of the c.1044+5G>A splice variant confirmed it affected RNA splicing by generating both a wild type and truncated transcript. We conclude that FOXP3 mutations can cause early-onset insulin-requiring diabetes with or without other features of IPEX syndrome.
Keywords: Diabetes Mellitus; Diabetes Mellitus, Type 1; Diarrhea; Forkhead Transcription Factors; Genetic Diseases, X-Linked; Humans; Immune System Diseases; Infant; Infant, Newborn; Male; Registries